Enhanced Localized Periodontitis Treatment with Azithromycin-Loaded Niosomal Thermosensitive Gels - Kunchorn Kerdmanee; Chuencheewit Thongsiri; Nuttawut Supachawaroj; Sucharat Limsitthichaikoon (OpenNano, 2025)
ABSTRACT: Periodontitis is a chronic inflammatory disease requiring localized drug delivery for sustained therapeutic action. Conventional treatments face challenges such as a rapid drug clearance and poor bioavailability. This study develops and evaluates an azithromycin-loaded niosomal thermoresponsive gel (AZG) to enhance drug retention and treatment efficacy. Azithromycin-loaded niosomes (AZN) were optimized using a 32 full factorial design with Span 60 and cholesterol, achieving nanoscale size, stable zeta potential, and high drug encapsulation. The optimized AZN was incorporated into a poloxamer 407-hyaluronic acid gel, ensuring in situ gelation and prolonged drug retention. AZG exhibited favorable gelation, biocompatibility, accelerated wound closure, enhanced cell proliferation, and significant anti-inflammatory effects (twofold IL-1β and sixfold TNF-α reduction, p < 0.05). By integrating sustained drug release with antibacterial and anti-inflammatory properties, AZG presents a promising adjunctive therapy for periodontitis, addressing key limitations of existing treatments.